Migraine and the development of additional psychiatric and pain disorders in the transition from adolescence to adulthood. (November 2021) - Gerstl, Lucia; Tadych, Natalie; Heinen, Florian; Kainz, Christine; Bonfert, Michaela V; Hannibal, Iris; Huss, Kristina; Ruscheweyh, Ruth; Straube, Andreas; Obermeier, Viola; von Kries, Rüdiger; Landgraf, Mirjam N
Introduction: The transition from childhood to adolescence and from adolescence to adulthood are vulnerable phases in life. In these phases, late or insufficient treatment of diseases may lead to chronification and favor development of additional disorders. In adolescents, migraine often has a highly negative impact on school performance and everyday life. The hypothesis of the present study was that adolescents with migraine have a higher risk for developing additional disorders such as psychiatric disorders or other pain syndromes in the course of the disease. Materials and methods: In this study, we analyzed health insurance data of 56, 597 German adolescents at the age of 15 years in the year 2006. By using the International Classification of Diseases (ICD 10), we determined a group with migraine diagnosis in the year 2006 and a control group without any headache diagnosis in 2006. We then compared both groups regarding the development of additional disorders (based on the ICD 10) during the following 10 years (2007 to 2016). Results: Adolescents with migraine had a 2.1 fold higher risk than persons without migraine diagnosis to develop an additional affective or mood disorder, a 1.8 fold higher risk to obtain neurotic, stress-related and somatoform disorders, a 1.8 fold higher risk to subsequently suffer from behavioral syndromes, a 1.6 higher risk to get back pain and a 1.5 fold higher risk for irritable bowel syndrome during the next 10 years. Conclusion: Adolescents with migraine are at risk for developing additional disorders later. Considering and addressing the patient's risks and potential medical and psychosocial problems might improve the long-term outcome significantly.